The Human Bocavirus 1 NP1 Protein Is a Multifunctional Regulator of Viral RNA Processing - Dong, Yanming (J Virol, 2018)
Human bocavirus 1 (HBoV1) encodes a genus-specific protein, NP1, which regulates viral alternative pre-mRNA processing. Similar to NP1 of the related bocavirus minute virus of canine (MVC), HBoV1 NP1 suppressed cleavage and polyadenylation of RNAs at the viral internal polyadenylation site (pA)p. HBoV1 (pA)p is a complex region. It contains 5 significant cleavage and polyadenylation sites, and NP1 was found to regulate only the three of these sites that are governed by canonical AAUAAA hexamer signals. HBoV1 NP1 also facilitated splicing of the upstream intron adjacent to (pA)p. Alternative polyadenylation and splicing of the upstream intron were independent of each other, functioned efficiently within an isolated transcription unit, and were responsive independent of NP1. Characterization of HBoV1 NP1 generalizes its function within the genus Bocaparvovirus, uncovers important differences, and provides important comparisons with MVC NP1 for mechanistic and evolutionary considerations. IMPORTANCE The Parvovirinae are small nonenveloped icosahedral viruses that are important pathogens in many animal species, including humans. The NP1 protein of human bocavirus 1 (HBoV1), similar to NP1 of the bocavirus minute virus of canine (MVC), regulates viral alternative RNA processing by both suppressing polyadenylation at an internal site, (pA)p, and facilitating splicing of an upstream adjacent intron. These effects allow both extension into the capsid gene and splicing of the viral pre-mRNA that correctly registers the capsid gene open reading frame. Characterization of HBoV1 NP1 generalizes this central mode of parvovirus gene regulation to another member of the bocavirus genus and uncovers both important similarities and differences in function compared to MVC NP1 that will be important for future comparative studies.